2010
DOI: 10.1016/j.jpsychires.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour skin conductance in panic disorder

Abstract: Skin conductance, physical activity, ambient temperature, and mood were recorded for 24 hours in 22 panic disorder (PD) patients and 29 healthy controls. During the day, subjects performed standardized relaxation tests (ARTs). We hypothesized that tonically elevated anticipatory anxiety in PD during waking and sleeping would appear as elevated skin conductance level (SCL) and greater skin conductance (SC) variability. Mean SCL was higher during both usual waking activities and sleeping in PD, but not during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
0
20
0
2
Order By: Relevance
“…SCL, a tonic measure, had a closer relationship with brain regions associated with anticipatory anxiety (for a discussion, see Parente et al, 2005) than did SC variability. A recent 24-hour monitoring study in panic disorder patients found SCL to be chronically elevated in these anxious patients compared to normal controls (Doberenz et al, 2010) while measures of phasic SC activation were not.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…SCL, a tonic measure, had a closer relationship with brain regions associated with anticipatory anxiety (for a discussion, see Parente et al, 2005) than did SC variability. A recent 24-hour monitoring study in panic disorder patients found SCL to be chronically elevated in these anxious patients compared to normal controls (Doberenz et al, 2010) while measures of phasic SC activation were not.…”
Section: Discussionmentioning
confidence: 80%
“…While this might not be necessary for ambient temperature and physical activity at the between-subject level, it is advisable at the within-subject level. In clinical studies using electrodermal measures, additional factors such as the effects of psychotherapeutic medication must also be taken into account as we discovered in our 24-hour panic disorder study (Doberenz et al, 2010). Even relatively healthy populations in developed countries are frequent users of over-the-counter and prescription medications with autonomic or central nervous system effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline levels of SCL have several implications for the development of internalizing symptoms. Abnormally high baseline SCL is linked to greater anxiety in participants reporting symptoms of generalized anxiety disorder (Pruneti et al 2010;Roth et al 2008) as well as panic disorder (Doberenz et al 2010). It has been hypothesized that individuals with high baseline SCL devote too many resources to environmental demands, resulting in longer periods of sympathetic activation (i.e., heightened arousal) and heightened risk for subsequent anxiety (Roth et al 2008).…”
Section: Autonomic Functioningmentioning
confidence: 99%
“…The complex pathogenesis of anxiety disorders is strongly influenced by genetic factors with heritability estimates ranging between 30 and 67% (Hettema et al, 2001). On a psychophysiological and neurocognitive level, hypervigilance and heightened physiological arousal as well as impaired attentional performance have been proposed as some of the key pathomechanisms of anxiety and panic disorder in particular (Craske and Simos, 2013;Doberenz et al, 2010;Eysenck, 1997;Eysenck et al, 2007;Howells et al, 2012;Meuret et al, 2011;Parente et al, 2005; for review see Geiger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%